2021
DOI: 10.1111/gcb.15971
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of heatwaves and micropollutants on freshwater ecosystems: Towards an integrated assessment of extreme events in multiple stressors research

Abstract: Freshwater ecosystems are strongly influenced by weather extremes such as heatwaves (HWs), which are predicted to increase in frequency and magnitude in the future. In addition to these climate extremes, the freshwater realm is impacted by the exposure to various classes of chemicals emitted by anthropogenic activities. Currently, there is limited knowledge on how the combined exposure to HWs and chemicals affects the structure and functioning of freshwater ecosystems. Here, we review the available literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 228 publications
1
48
1
Order By: Relevance
“…Warming, on the other hand, showed less clear effects and may not always threaten the macrophyte-dominated state. In fact, in combination with the pesticides, it may show either antagonistic or synergistic effects [37]. Pesticides have been shown to degrade faster at higher temperatures [38], but in both our micro-and mesocosms, pesticide decline did not differ between the two temperatures.…”
Section: The Role Of Community Complexity In Upscalingmentioning
confidence: 68%
“…Warming, on the other hand, showed less clear effects and may not always threaten the macrophyte-dominated state. In fact, in combination with the pesticides, it may show either antagonistic or synergistic effects [37]. Pesticides have been shown to degrade faster at higher temperatures [38], but in both our micro-and mesocosms, pesticide decline did not differ between the two temperatures.…”
Section: The Role Of Community Complexity In Upscalingmentioning
confidence: 68%
“…For example, Nõges et al ( 2016 ) identified European waters with up to seven co‐acting stressors, although two co‐acting stressors were the most common, being identified in 42% of cases. Similarly, there have been calls for investigating the responses to stressors at multiple levels of intensity (Polazzo et al, 2021 ; Schäfer & Piggott, 2018 ), since responses at low and high stressor intensities may differ greatly (Beaumelle et al, 2020 ; Dixon et al, 2020 ) and result in different interactions being detected (Ma et al, 2020 ). In both cases, sample sizes will need to be even larger than for two stressors each at a single intensity, and as we have already found, many experiments are probably greatly underpowered even in this simpler scenario.…”
Section: Consequences and Recommendationsmentioning
confidence: 99%
“…At the individual level, responses to multiple stressors might be assessed by their joint effect on the physiology of an organism, e.g., a decline in feeding, growth, or fecundity, or a biochemical change (Nõges et al, 2016 ), and may also be measured on survival rates (e.g., bee health responses to agrochemicals, Siviter et al, 2021 ). Population responses to multiple stressors may be assessed by monitoring densities, biomass, or other markers such as chlorophyll concentrations (e.g., freshwater population responses to combinations of invasive species, pesticides, temperature, or UV changes, Burgess et al, 2021 ), whereas ecosystem responses might be measured through multiple stressor effects on functional and taxonomic diversity (e.g., coral reef species richness responses to warming and acidification, Timmers et al, 2021 ), or through other measures of ecosystem integrity (e.g., stability, Polazzo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nõges et al (2016) identified European waters with up to seven co-acting stressors, although two co-acting stressors were the most common, being identified in 42% of cases. Similarly, there have been calls for investigating the responses to stressors at multiple levels of intensity (Polazzo et al 2021;Schäfer and Piggott, 2018), since responses at low and high stressor intensities may differ greatly (Beaumelle et al, 2020;Dixon et al, 2020) and result in different interactions being detected (Ma et al, 2020). In both cases, sample sizes will need to be even larger than for two stressors each at a single intensity, and as we to detect a non-additive interaction between two stressors should not be associated with conclusions that the interaction is additive, only that there is insufficient evidence to show otherwise.…”
Section: Consequences and Recommendationsmentioning
confidence: 99%
“…coral reef species richness responses to warming and acidification, Timmers et al 2021), or through other measures on ecosystem integrity (e.g. stability, Polazzo and Rico, 2021).…”
Section: Introductionmentioning
confidence: 99%